ChemInform Abstract: Silver‐Mediated Oxidative Aliphatic C—H Trifluoromethylthiolation. Issue 30 (July 2015) - Guo, Shuo; Zhang, Xiaofei; Tang, Pingping
Abstract A practical and direct trifluoromethylthiolation reaction of unactivated aliphatic C—H bonds is developed employing a silver‐based reagent.